Adverse childhood experiences and subjective happiness: Half-longitudinal mediation role of family sense of coherence - Erus, Seher Merve; Uygun, Ezgi Gueney; Deniz, M. Engin; Satici, Seydi Ahmet (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Family relationships are crucial for an individual's capacity to live a healthy life. Healthy family relationships depend on family coherence, which also has an impact on an individual's happiness. Previous studies have highlighted that adverse childhood experiences (ACEs) can influence the quality of family life and family coherence. Thus, ACEs can harm the family's cohesion and, as a result, lower subjective happiness. In this study, the mediation of family sense of coherence was investigated in the ACEs-subjective happiness link. Participants include 308 individuals (mean age = 26.06). The data was collected through self-reported questionnaires and analyzed using cross-lagged structural equation modeling. Results of the cross-lagged panel model for a halflongitudinal design indicated that family sense of coherence had a significant mediation role in the association between ACEs and subjective happiness. The findings show that low family coherence reduces the subjective happiness of people with ACEs. As a result, adults' happiness may be impeded by ACEs as well as dysfunctional family dynamics and cohesiveness. It is possible to deduce that a sense of family cohesion will be a healing factor for adults who have had ACEs, and that happiness will rise as family cohesion increases.
Keywords: Adverse childhood experiences; Family coherence; Subjective happiness; Half-longitudinal; EMOTION REGULATION; SOCIAL SUPPORT; HEALTH; PERFECTIONISM; SATISFACTION; ADOLESCENTS; PERSONALITY; OUTCOMES; STRESS; ADULTS; Psychology